Exploring macro-environmental catalysts and barriers of healthcare 4.0 transformation in Central-Eastern European countries: A comprehensive study in Hungary - Halmosi, Péter; Aranyossy, Márta (Technology in society, 2024)
The pursuit of a secure, efficient healthcare system responsive to patient needs remains a crucial goal for developed countries. Governments, grappling with rising healthcare demands, are increasingly turning to technological innovation as a transformative solution. Healthcare 4.0, integrating cutting-edge industrial technologies, aims to enhance patient experience, promote health, control costs, and boost clinical satisfaction. The COVID-19 pandemic has catalysed investments in digitalisation, but the promises of Healthcare 4.0 are still seemingly unrealized. This is especially true in the Central-Eastern European (CEE) region, particularly in Hungary, where substantial Industry 4.0 innovation potential intersects with shrinking financial resources, a challenging political environment, a transitioning healthcare system hindering the widescale transition to Healthcare 4.0. Thus, this paper aims to explore the macro-environmental factors influencing Healthcare 4.0 adoption in Hungary. Leveraging qualitative content analysis of interviews with 21 Hungarian healthcare technology startup founders, we aim to map the catalysts and barriers of a Healthcare 4.0 transition using a PESTLE framework. This explorative study contributes to the literature with valuable insights from the innovators' perspective, serving as a foundation for future policy interventions in the quest for widespread Healthcare 4.0 implementation. •Unveiling catalysts and barriers of Healthcare 4.0 transformation in CEE with PESTLE providing a comprehensive framework.•Identifying key barriers: declining government healthcare spending, regulatory obstacles and social acceptance.•Featuring key catalysts: rising healthcare demand, efficiency effects of innovations and potentials of systemic data sharing.•Prioritizing healthtech entrepreneurs' perceptions is vital for supportive healthcare policies.